2014
DOI: 10.3892/mmr.2014.2212
|View full text |Cite
|
Sign up to set email alerts
|

Role and mechanism of Twist1 in modulating the chemosensitivity of FaDu cells

Abstract: Multidrug resistance (MDR) is one of the most important obstacles affecting the efficacy of chemotherapy treatments for numerous types of cancer. In the present study, we have demonstrated the possible function of Twist1 in the chemosensitivity of head and neck squamous cell carcinoma (HNSCC) and have identified that its mechanism maybe associated with MDR1/P-gp regulation. To investigate this, the hypopharyngeal cancer cell line, FaDu, and its MDR cell line induced by taxol, FaDu/T, were employed. Stable tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…Interestingly, a high expression of the TWIST1 gene was found to correlate with a poor radioresponse, suggesting that there may be a link between a mesenchymal phenotype and radioresistance in HNSCC. This is in line with the finding that overexpression of Twist1 enhances the resistance to apoptosis in the human hypopharyngeal carcinoma cell line FaDu and with our previous study where cells of the mesenchymal‐like CD44 high /EGFR low subpopulation of HNSCC cell lines were shown to be less sensitive to radiotherapy than their epithelial counterparts . Moreover, in a meta‐analysis, Twist1 was shown to correlate with low differentiation, lymph node metastasis, and local recurrence, features that all may be associated with an increased EMT phenotype of the tumor .…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, a high expression of the TWIST1 gene was found to correlate with a poor radioresponse, suggesting that there may be a link between a mesenchymal phenotype and radioresistance in HNSCC. This is in line with the finding that overexpression of Twist1 enhances the resistance to apoptosis in the human hypopharyngeal carcinoma cell line FaDu and with our previous study where cells of the mesenchymal‐like CD44 high /EGFR low subpopulation of HNSCC cell lines were shown to be less sensitive to radiotherapy than their epithelial counterparts . Moreover, in a meta‐analysis, Twist1 was shown to correlate with low differentiation, lymph node metastasis, and local recurrence, features that all may be associated with an increased EMT phenotype of the tumor .…”
Section: Discussionsupporting
confidence: 88%
“…TWIST expression is elevated in hepatocellular carcinoma, breast cancer, nasopharyngeal carcinoma and oral carcinoma (21,(23)(24)(25). Previous studies have revealed a novel function of TWIST, and it has been reported to be involved in the development of acquired chemoresistance in human cancer cells (15,16,26). In the present study, TWIST and MDR1 were expressed to a significantly higher level in liver tissues compared with in non-cancerous tissues.…”
Section: Discussionsupporting
confidence: 55%
“…Consistent with a previous report (14), it was revealed that TWIST is involved in the development of acquired drug resistance in human cancer cells. TWIST overexpression is also correlated with chemotherapy resistance in various types of cancer and leads to a poorer prognosis (15,16). Therefore, TWIST may be considered a novel therapeutic target in overcoming MDR in liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Reverse transcription (RT)-PCR and sequencing. Total RNA was extracted and RT-PCR was conducted as previously described (10). The annealing temperature was 56-58˚C for AFP and 60˚C for ÎČ-actin amplification.…”
Section: Methodsmentioning
confidence: 99%